Evaluation of a Hypersensitivity Inhibitor Containing a Novel Monomer That Induces Remineralization-A Case Series in Pediatric Patients - Manami Tadano; Aya Yamada; Yuriko Maruya; Ryoko Hino; Tomoaki Nakamura; Seira Hoshikawa; Satoshi Fukumoto; Kan Saito (MDPI AG, 2021)
Background: Recently, tooth deformities have been frequently encountered by pediatric dentists. Severe enamel hypomineralization sometimes induces pain such as hyperesthesia, but composite resin restoration is difficult because it often detaches without any cavity preparation. Resin-based hypersensitivity inhibitors for tooth physically seal the dentinal tubules. It was reported that hypersensitivity inhibitor containing novel adhesive monomers forms apatite and induces remineralization in vitro. Therefore, these case series assessed the clinical effects of remineralization and the suppression of hypersensitivity by Bio Coat Ca (Sun Medical, Shiga, Japan). Methods: After mechanical tooth cleaning was performed, the hypersensitivity inhibitors were applied and cured by light exposure. Changes in hypersensitivity were determined by visual analog scale (VAS). The improvement of hypomineralization was evaluated by the change in color tone based on the digital images of intraoral photographs. Results: After repeated monthly treatments, these cases showed decreased hypersensitivity after the fourth application, while the opaque white and brownish color improved on the seventh application. Conclusion: This novel hypersensitivity inhibitor with calcium salt of 4-methacryloxyethyl trimellitic acid (C-MET) and 10-methacryloyloxydecyl dihydrogen calcium phosphate (MDCP) not only suppressed hypersensitivity but also improved cloudiness and brown spots in recently erupted permanent teeth in presented cases.